Family resilience of families with parental cancer and minor children: a qualitative analysis - Heuser, Christian; Schneider, Juliane Nora; Heier, Lina; Ernstmann, Nicole; Nakata, Hannah; Petermann-Meyer, Andrea; Bremen, Rebecca; Karger, André; Icks, Andrea; Brümmendorf, Tim H.; Geiser, Franziska (Frontiers in Psychology, 2024)
Introduction Estimated 50,000 minor children in Germany experience a newly diagnosed cancer in one of their parents every year. Family resilience has proven to be an important concept against life crises. However, little research exists regarding family resilience in the context of parental cancer with minor children. Based on the “Family Resilience Framework,” the aim of the study is to investigate the processes of family resilience of affected families. In addition, we explore which combinations of promoting family resilience processes can be characterized. Methods As part of the mixed-method quasi-experimental interventional study “F-SCOUT,” a qualitative content analysis was used to analyze the documentation of the “Family-Scouts” (a fixed contact person who advises, accompanies, and supports the families). Documentation was performed by families’ study inclusion (T0), after 3 months (T1) and 9 months (T2) concerning current family situation, organization of everyday life, emotional coping, open communication within the family, and planned tasks. Results The N = 73 families had between one and six children. In 58 (79%) families, the mother had cancer. In the course of the analysis, a category system with 10 main categories and 36 subcategories emerged. Family resilience processes were described to different extents. Combinations of categories promoting family resilience were characterized by the use of social resources, flexibility, economic resources, and open communication. Discussion The findings are consistent with existing assumptions about family resilience in terms of the importance of social resources, family cohesion, mutual support, flexibility, open communication, and psychological well-being. In contrast to the findings of previous research, spirituality, and collaborative problem-solving indicate less centrality here. In turn, the findings on economic resources and information-seeking provide a valuable addition to the family resilience literature in the context of parental cancer with minor children. Clinical trial registration ClinicalTrials.gov, identifier NCT04186923.